How Self-Appraisal Is Mediated by the Brain - Knyazev, Gennady G.; Savostyanov, Alexander N.; Bocharov, Andrey V.; Rudych, Pavel D. (Frontiers in Human Neuroscience, 2021)
Self-appraisal is a process that leads to the formation of self-esteem, which contributes to subjective well-being and mental health. Neuroimaging studies link self- esteem with activity of the medial prefrontal cortex (MPFC), right temporoparietal junction (rTPJ), posterior cingulate cortex (PCC), anterior insula (AIns), and dorsolateral prefrontal cortex. It is not known, however, how the process of self-appraisal itself is mediated by the brain and how different nodes of the self-appraisal network interact with each other. In this study, we used multilevel mediation analysis of fMRI data recorded during the trait adjective judgement task, treating emotional valence of adjectives as the predictor, behavioral response as the dependent variable, and brain activity as the mediator. Mediation effect was revealed in the rTPJ. Dynamic causal modeling showed that positive self-descriptions trigger communication within the network, with the rTPJ exerting the strongest excitatory output and MPFC receiving the strongest excitatory input. rAIns receives the strongest inhibitory input and sends exclusively inhibitory connections to other regions pointing out to its role in the processing of negative self-descriptions. Analysis of individual differences showed that in some individuals, self-appraisal is mostly driven by the endorsement of positive self-descriptions and is accompanied by increased activation and communication between rTPJ, MPFC, and PCC. In others, self-appraisal is driven by the rejection of negative self-descriptions and is accompanied by increased activation of rAIns and inhibition of PCC and MPFC. These groups’ membership was predicted by different personality variables. This evidence uncovers different mechanisms of the positive self-bias, which may contribute to different facets of self-esteem and are associated with different personality profiles.